Dribbling techniques - Giordano, L.; Ceciliani, A.; Izzo, R.; D'Elia, F. (Journal of Human Sport & Exercise, 2019)
The teaching methodology in juvenile football features various approaches, spanning from prescriptive teaching to heuristic learning. The aim of this research is to theoretically point out which of the two below is the most proficient way of improving the dribbling qualities: 1) Making the pupils steadily repeat the same exercise under the coaches' eyes; 2) Letting the kids free to express their own abilities avoiding the use of a pre-packaged schedule. All along the process, the teacher catches up with the most updated existing knowledge in the field of motoric learning. The first method sets an ascending degree of difficulty beginning with low-intensity exercises right up to a tougher dribbling making. The little boys are firstly requested to lift the ball with their hands up until the moment when they are expected to do it with the sole use of their feet. On the contrary, the second method grants the young learners complete freedom. Although they are not given any rules, they are asked to reach the best dribbling quality by doing their utmost. All in all, that those who proceed under the teacher's prescriptions acquire a better knowledge shows that the traditional system is the only possible option.